2005
DOI: 10.1364/ao.44.004693
|View full text |Cite
|
Sign up to set email alerts
|

White-light optical particle spectrometer for in situ measurements of condensational growth of aerosol particles

Abstract: A new optical particle counter was developed to provide fast in situ sizing of cloud droplets in the Leipzig Aerosol and Cloud Interaction Simulator (LACIS). The new instrument features white light for the illumination of the sampling volume: two off-axis elliptical mirrors, providing a wide angle of collection for light scattered by particles; and an optically defined sampling volume. The smooth unambiguous response characteristic for water droplets allows direct conversion of the measured signal amplitudes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The lens focuses the scattered light to a spot that is off-axis from the lens center on the opposite side of the drilled hole, leading to clear physical separation of the laser beam and focused scattered light. Kiselev et al (2005) have reported a similar design. Instead of the modified lens in our design, they used a pair of customdesigned off-axis elliptical mirrors.…”
Section: Basic Design Conceptmentioning
confidence: 71%
“…The lens focuses the scattered light to a spot that is off-axis from the lens center on the opposite side of the drilled hole, leading to clear physical separation of the laser beam and focused scattered light. Kiselev et al (2005) have reported a similar design. Instead of the modified lens in our design, they used a pair of customdesigned off-axis elliptical mirrors.…”
Section: Basic Design Conceptmentioning
confidence: 71%
“…LACIS consists of a laminar flow tube and an white-light optical particle spectrometer (OPS, Kiselev et al, 2005) that measures the size of particles after the passage through the tube. For this study, a flow tube length of 1 m was used for LACIS.…”
Section: Lacismentioning
confidence: 99%
“…At the outlet of the flow tube, the number concentration and size of the humidified particles was measured with an optical particle spectrometer that has been designed and built especially for LACIS (for details see Kiselev et al, 2005). A xenon-arc lamp provided white light for the measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the measured PSL signals, the modeled PSL response curve, and an exemplary response curve for NaCl particles with a dry diameter of 50 nm. Response curves calculated for solutions account for changes in the particle refractive index with changing particle concentration (see Kiselev et al, 2005). For the experiment introduced in this work, the smallest detectable size was about 250 nm when the full intensity of the light source of the optical particle spectrometer was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation